The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0162353215578277
|View full text |Cite
|
Sign up to set email alerts
|

Inequitable Access to Gifted Education

Abstract: This study examined discrepancies in educational opportunity for gifted students at the program services level. School districts in the study (N = 1,029) varied in expenditures for gifted education and the allocation of faculty for gifted education. The relationships of variables representing funding and staffing gifted education and school contextual variables such as locale (city, suburban, town, rural) were examined. Pairwise comparisons among locales revealed effect sizes as high as 0.31 with respect to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 29 publications
2
46
1
Order By: Relevance
“…While Baker (2001a;2001b) and Kettler et al (2015) found variation in gifted education services by district/school size or available resources, other than the cases mentioned above, this was not the case in the sample states and districts in this study.…”
Section: Variation By Size and Resourcescontrasting
confidence: 62%
See 3 more Smart Citations
“…While Baker (2001a;2001b) and Kettler et al (2015) found variation in gifted education services by district/school size or available resources, other than the cases mentioned above, this was not the case in the sample states and districts in this study.…”
Section: Variation By Size and Resourcescontrasting
confidence: 62%
“…Recent research indicates that gifted services offered in districts and/or schools continue to vary relative to district/school size, as Kettler, Russell, and Puryear (2015) found that small rural school districts spend less money per student in gifted education, allocate a smaller proportion of their overall budget to gifted services, and allocate less money for faculty in gifted. Additionally, school size and locale were the strongest predictors of variance in funding and staffing across all contextual variables (Kettler et al, 2015).…”
Section: Identification Policies and Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because schools are federally required to provide special education services to students with disabilities, yet gifted programming is dictated by state or district requirements, students may have uneven access to services simply based on where they attend school. In a study of Texas school districts, researchers found that rural schools, small schools, and schools with higher percentages of low-income students often provided students with fewer opportunities for gifted and talented education compared to schools in other areas (Kettler, Russell, & Puryear, 2015). Lack of resources for rural districts in particular is commonly noted as a concern for gifted students, as districts can be unwilling or unable to provide academic enrichment opportunities (Howley, Rhodes, & Beall, 2009).…”
Section: Diversity Considerations For Gifted and Twice-exceptional Stmentioning
confidence: 99%